Review of Temperature and Humidity Impacts on RF Signals - Natalie Chen Yi, Lim; Lisa, Yong; Hieng Tiong, Su; Abel Yu Hao, Chai; Chamath Kanalaka, Vithanawasam; Yi Lung, Then; Fei Siang, Tay (2020)
Signal strength of radio waves propagating from transmitter to receiver can be affected by atmospheric conditions even in line-of-sight situation. These atmospheric conditions cause the propagated waves to vary from the anticipated range. Higher frequencies can result in weak signals as they have shorter wavelengths. High frequency increases the chances of hitting obstacles such as water molecules in the atmosphere when radio waves propagate. This will cause a weakening effect as water absorbs some of the energy from the waves and scatters the rest of it. This means that a higher humidity can weaken the signal strength while a higher temperature can enhance the signal strength of the radio waves. Although few studies have been carried out to explore the effect of atmospheric conditions on signal strength, there have been contradictory results and conclusions. Some research studies claimed that humidity was the main factor while others claimed that temperature was the dominating factor. These researchers conducted their experiments in different kinds of weather or seasons. Most of the experiments were conducted using hygrometers, thermometers, humidity and temperature sensors and weather monitoring devices to measure the temperature and humidity during the experiment. Radio signal strength was measured using Cable Access Television Analyzers or Spectrum Analyzers. The frequency used in these experiments ranges between Very High Frequency (VHF) and Ultra High Frequency (UHF) where they provide different network services. This work aims to study the effect of temperature and humidity towards signal strength. Statistical analysis is performed using results from existing researches on the relationship between radio signal strength range from 100MHz to 2.4GHz with temperature and humidity. The statistical results performed in this paper use the Pearson Correlation Coefficient and p-value to show that temperature and humidity do have an impact on radio signals.